Efektivitas Media Komik Digital Flipbook dan Gambar Berseri Terhadap Keterampilan Menulis Cerpen Siswa - Yasmin, Putri; Hilaliyah, Tatu; Firmansyah, Dodi (Universitas Islam Sumatera Utara, 2025)
Short story writing is a complex skill that many students struggle to master, often resulting in a lack of enthusiasm for learning the craft in formal educational settings. This study aims to investigate the effect of flipbook-based digital comic media, the effect of serial image media, and the comparative impact of both media on the short story writing skills of Grade XI students at MAN 3 Tangerang. Employing an experimental research method with a pretest-posttest control group design, the study used a simple random sampling technique, selecting class XI Science 3 as the experimental group and XI Science 4 as the control group. Research data were collected through students’ short story writing tasks administered during both pretest and posttest stages. The findings revealed a pretest-posttest improvement in the experimental group using flipbook-based digital comics (45.40 to 71.60), while the control group using serial images improved from 43.20 to 70.60. Despite a slight performance advantage in favor of the digital comic group, the difference was not statistically significant. Therefore, both flipbook-based digital comics and serial images are equally effective in enhancing students’ short story writing skills.